(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
In today’s sports of high achievements, additional influencing factors that contribute to increasing the level of sportsmanship amongst men and women play an important role. Among them is training in conditions of natural hypoxia, which, under the condition of rationally planned loads, largely determine the results achieved by athletes in competitions. This also applies in the training process of highly qualified male and female boxers. The aim of the study. Determine the dynamics of indicators of physical fitness of boxer cadets of the team of higher military educational institutions (in this example from the National Academy of Ground Forces of P. Sahaidachny) in the conditions of educational and training meetings in the highlands in the pre-competition period. Material and methods. 23 cadets - members of the men’s (n=12) and women’s (n=11) national boxing teams of the Academy participated in the study. The ascertainment experiment lasted for four weeks, testing the level of physical fitness took place four times. Changes in indicators of speed, power endurance, speed-power qualities, strength and coordination abilities were evaluated. The results. During the pedagogical experiment, across the stages of testing, we observed mostly positive dynamics of physical qualities in both women and men, while only at certain stages we observed statistically significant changes in some physical qualities (p<0.05). At the same time, as a result, analyzing the initial and final results of the tests, we obtained statistically significant changes in most indicators (p<0.05), with the exception of the dynamometry of the left hand in women, and the right hand in men (p>0.05). Conclusions. The effectiveness of the training of male and female boxers in the conditions of the highlands has been experimentally confirmed, provided that rational physical exercises are well planned, taking into account the level of individual capabilities of male and female athletes in relation to the level of their physical fitness in general.